Talaromyces (Penicillium) marneffei and Mycobacterium tuberculosis coinfection in a HIV negative patient in Amritsar Punjab, India - Chalana, Manvy; Oberoi, Loveena (Tropical Journal of Pathology and Microbiology, 2019)
A 54-year-old, male patient with a history of Pulmonary Tuberculosis and Diabetes mellitus for the past 20 years was admitted to a tertiary care hospital with chief complaints of high-grade fever with chills, productive cough and a one month history of loss of appetite and generalized malaise. On FNAC of cervical lymph nodes; impression of tubercular pathology (AFB positive) was reported. Talaromyces (Penicillium) marneffei and Mycobacterium tuberculosis co-infection was confirmed. Talaromyces marneffei (Penicillium marneffei) is a thermally dimorphic fungus that can cause severe infections particularly in immunocompromised patients was first discovered in 1956 in the regions of Southeast Asia. It exists as mycelia form at 25 °C and yeast like form at 37 °C. A large number of T. marneffei infected patients who are HIV negative have been reported in recent years.